The persistence of snow on the ground affects the shape of streamflow hydrographs over space and time: a continental-scale analysis - Le, Edward; Janssen, Joseph; Hammond, John; Ameli, Ali A. (Frontiers in Environmental Science, 2023)
Snow persistence (SP) is a widely available remotely-sensed measure of snowpack accumulation and ablation, reflecting the duration of snow presence on the ground in a given year. Available local-scale studies showed that SP is associated with the average magnitude of streamflow. However, despite the intuitive relationship between SP and catchment storage/release functioning, the spatial and temporal links between the persistence of snow on the ground and the shape and functionality of streamflow hydrographs were not studied empirically and were not generalized to diverse climatic settings. This study empirically explores the spatial and temporal links that SP has with measures of hydrograph shape and variability during low-flow and high-flow conditions across continent-wide gradients of aridity and seasonality. In arid in-phase and wet out-of-phase climates, higher SP is spatially associated with a damper (i.e., less flashy) streamflow hydrograph during low-flow and high-flow conditions. This is shown by a larger ratio of baseflow to average flow, a larger ratio of extreme lowflow to average flow, lower low-flow variability, and lower high-flow variability. While SP is spatially associated with a damped hydrograph in both climatic regions, the relationship is stronger in arid/in-phase climates compared to wet/out-of-phase climates. For example, the size of the nonlinear impact of SP on reducing low-flow and high-flow variabilities is larger in arid in-phase climates (-7.64, -3.44, respectively) than in wet out-of-phase climates (-4.34, -2.02, respectively). Temporal analyses for "typical snow-rich" catchments show that years with relatively higher SP may lead to relatively flashier streamflow hydrographs, with lower baseflow indices, lower ratios of extreme lowflow to average flow, higher ratios of extreme high-flow to average flow and higher high-flow variability. Such results (1) demonstrate the utility of SP as a globally available descriptor of streamflow hydrograph shape and variability in a wide diversity of climatic conditions, (2) highlight that climate-driven snow loss may lead to substantial changes to hydrograph form and functionality, and (3) indicate that space-time symmetry may not be a valid assumption in hydrology.